The captive heart - Cramer, W. Dale. (Minneapolis, Minn. : Bethany House, 2012)
As a displaced Amish community struggles in a lawless Mexico, a forbidden love blossoms, and one man is pushed to the limits of his convictions.
Keywords: Amish -- Fiction; Frontier and pioneer life -- Fiction; Mexico -- Fiction; Christian fiction; Love stories; Historical fiction